Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the value of \( a \) in the quadratic function \( y = ax^2 + bx + c \), we'll use the given table of values.
We have these points:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline 0 & -3 \\ \hline 1 & -3.75 \\ \hline 2 & -4 \\ \hline 3 & -3.75 \\ \hline 4 & -3 \\ \hline 5 & -1.75 \\ \hline \end{array} \][/tex]
First, we use the point \((0, -3)\):
[tex]\[ y = ax^2 + bx + c \\ -3 = a(0)^2 + b(0) + c \Rightarrow c = -3 \][/tex]
Now, let's use the points \((1, -3.75)\) and \((2, -4)\).
For \((1, -3.75)\):
[tex]\[ -3.75 = a(1)^2 + b(1) + c \\ -3.75 = a + b - 3 \\ a + b - 3 = -3.75 \Rightarrow a + b = -0.75 \][/tex]
For \((2, -4)\):
[tex]\[ -4 = a(2)^2 + b(2) + c \\ -4 = 4a + 2b - 3 \\ 4a + 2b - 3 = -4 \Rightarrow 4a + 2b = -1 \][/tex]
Now we have the system of linear equations:
[tex]\[ 1) \quad a + b = -0.75 \\ 2) \quad 4a + 2b = -1 \][/tex]
To solve this system, we can use substitution. From the first equation:
[tex]\[ a + b = -0.75 \Rightarrow b = -0.75 - a \][/tex]
Substitute this into the second equation:
[tex]\[ 4a + 2(-0.75 - a) = -1 \\ 4a - 1.5 - 2a = -1 \\ 2a - 1.5 = -1 \\ 2a = 0.5 \\ a = 0.25 \][/tex]
Hence, the value of \( a \) in the function's equation is:
[tex]\[ \boxed{\frac{1}{4}} \][/tex]
So, the correct answer is:
D. [tex]\(\frac{1}{4}\)[/tex]
We have these points:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline 0 & -3 \\ \hline 1 & -3.75 \\ \hline 2 & -4 \\ \hline 3 & -3.75 \\ \hline 4 & -3 \\ \hline 5 & -1.75 \\ \hline \end{array} \][/tex]
First, we use the point \((0, -3)\):
[tex]\[ y = ax^2 + bx + c \\ -3 = a(0)^2 + b(0) + c \Rightarrow c = -3 \][/tex]
Now, let's use the points \((1, -3.75)\) and \((2, -4)\).
For \((1, -3.75)\):
[tex]\[ -3.75 = a(1)^2 + b(1) + c \\ -3.75 = a + b - 3 \\ a + b - 3 = -3.75 \Rightarrow a + b = -0.75 \][/tex]
For \((2, -4)\):
[tex]\[ -4 = a(2)^2 + b(2) + c \\ -4 = 4a + 2b - 3 \\ 4a + 2b - 3 = -4 \Rightarrow 4a + 2b = -1 \][/tex]
Now we have the system of linear equations:
[tex]\[ 1) \quad a + b = -0.75 \\ 2) \quad 4a + 2b = -1 \][/tex]
To solve this system, we can use substitution. From the first equation:
[tex]\[ a + b = -0.75 \Rightarrow b = -0.75 - a \][/tex]
Substitute this into the second equation:
[tex]\[ 4a + 2(-0.75 - a) = -1 \\ 4a - 1.5 - 2a = -1 \\ 2a - 1.5 = -1 \\ 2a = 0.5 \\ a = 0.25 \][/tex]
Hence, the value of \( a \) in the function's equation is:
[tex]\[ \boxed{\frac{1}{4}} \][/tex]
So, the correct answer is:
D. [tex]\(\frac{1}{4}\)[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.